PREDIKSI ZONASI PENERIMAAN PESERTA DIDIK BARU SEKOLAH DASAR NEGERI TAHUN 2020-2024 DENGAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (Studi Kasus : Kecamatan Tembalang) - Aulia Budi Andari; Bandi Sasmito; Hana Sugiastu Firdaus (Jurnal Geodesi UNDIP, 2020)
ABSTRAKKementerian Pendidikan dan Kebudayaan (Kemendikbud) telah mengumumkan sistem yang digunakan untuk program Pendaftaran Peserta Didik Baru (PPDB). Menindaklanjuti peraturan tersebut, Pemerintah Kota Semarang merancang kebijakan dengan menerapkan sistem zonasi untuk PPDB 2019/2020. Pada penelitian ini, kajian lebih dalam sistem zonasi sekolah dasar dilakukan di Kecamatan Tembalang. Sistem zonasi yang dirancang adalah berdasarkan peraturan pemerintah, sedangkan metode spasial thiessen polygon akan membagi area sesuai dengan sebaran sekolah yang ada di Kecamatan Tembalang. Kedua metode ini digunakan untuk mengidentifikasi perbedaan antar zonasi berdasarkan peraturan dan secara spasial. Selanjutnya, analisis jaringan juga dilakukan untuk mengetahui keterjangkauan sekolah ke pemukiman yang ada, baik dengan berjalan kaki maupun berkendara. Kemudian, barulah diprediksi daya tampung sekolah dasar negeri tahun 2020 hingga 2024 dengan menggunakan data daya tampung sekolah dasar dan data kelahiran tahun 2013 hingga 2017, sehingga dapat diketahui tercukupi atau tidaknya daya tampung sekolah dasar negeri tahun 2020 hingga 2024 di Kecamatan Tembalang. Pemetaan sebaran sekolah di Kecamatan Tembalang menunjukan bahwa Kecamatan Tembalang memiliki 21 sekolah dasar negeri yang tersebar di tiap kelurahan dengan sekolah dasar negeri terbanyak terdapat di Kelurahan Sendangmulyo dan Tandang. Kelurahan  ABSTRACTThe Ministry of Education and Culture has announced the system used for the New Student Registration (PPDB) program. Following up on this regulation, the Semarang City Government designed a policy by implementing a zoning system for PPDB 2019/2020. In this study, a deeper study of the primary school zoning system was carried out in Tembalang Sub-District. The zoning system that is created is based on government regulations, while the spatial method of thiessen polygon will divide the area according to the distribution of schools in the Tembalang District. Both of these methods are used to identify differences between zoning based on regulations and spatial. Furthermore, network analysis is also carried out to determine the affordability of schools to existing settlements, either on foot or by vehicle. Then, it is predicted that the capacity of state primary schools in 2020 to 2024 is using the data of primary school capacity and birth data from 2013 to 2017, so that the capacity of state primary schools in 2020 to 2024 in Tembalang District can be known. Mapping the distribution of schools in Tembalang Sub-District shows that Tembalang Sub-District has 21 public elementary schools in each village with the highest number of public primary schools in Sendangmulyo and Tandang. The village that has no primary school at all is Jangli. Comparison of school zoning based on government regulations and spatial analysis using thiessen polygon shows that the two zonations have similarities with the government zoning of 61 zones and thiessen polygon with 62 zones. The village that can reach out the closest school within 15 minutes is Sendangguwo. The village that reach out the school within 60 minutes is Jangli with an area of 40,985 ha (49.76%). PPDB modeling was carried out from 2020 to 2023 due to the similarity of data between 2023 and 2024. Overall, the capacity in Tembalang Sub-District from 2020 to 2023 have the greatest excess of students consist in 2021 is 3.495 students and the smallest excess of students consist in 2022 is 669 students..